Pravo dioničara zahtijevati obvezno sklapanje ugovora o prodaji dionica - Zubović, Antonija (Podjetje in delo, 2025)
The paper analyses the provision of Article 49 of the Croatian Takeover Act according to which any shareholder of the target company may, if the offeror does not publish a takeover bid, under the conditions and in the manner provided by the Act, file a lawsuit before the commercial court with territorial jurisdiction demanding the mandatory conclusion of a share sale agreement under the conditions under which the takeover bid should have been published. The authors separately address the issues of jurisdiction for determining the obligation to publish a takeover bid, active and passive standing, the moment when a claim can be filed, the time limit for bringing an action for mandatory conclusion of the agreement, the form of the share sale agreement, and the amount of the claim. A review of the case law of national courts shows that there are different interpretations of the cited provision, which lead to inconsistent case law and, ultimately, result in legal uncertainty. However, despite the perceived inconsistency of court practice, the authors oppose the proposal to delete the provision of Article 49 of the Takeover Act, as this would lead to the deprivation of the rights of minority shareholders that were given to them by the Takeover Act in 2002, and would also be against the purpose and goal of the Takeover Act, which is the protection of minority shareholders. Also, they advocate the certainty and precision of the legal norm, which will ensure clarity and predictability in its application.
Keywords: Croatian law; delnice; delničarji; Hrvaška; hrvatsko pravo; mandatory conclusion of share sale agreement; obvezno sklapanje ugovora o prodaji dionica; ponuda za preuzimanje; postopek prevzema; postupak preuzimanja; preuzimanje dioničkih društava; prevzemi; prodaja delnic; protection of minority shareholders; sanctions for non-publishing a takeover bid; sankcije za neobjavljivanje ponude za preuzimanje; takeover bid; takeover procedure; takeovers; zaščita manjšinskih delničarjev; zaštita manjinskih dioničara